2022
DOI: 10.3103/s0147688222030078
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of University Students to the Information Content of Electronic Educational Platforms

Abstract: Due to the widespread transition of universities to a remote work format, a survey of students was conducted to identify information-content characteristics and the attitudes of university students to electronic educational platforms. The study took place in two stages from September 2020 to November 2021. Surveys were conducted using Google forms and the MS Teams platform, as well as observations and interviews. The respondents were students at several Russian universities. The legal framework for educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They are used as an alternative to desktop apps. Research analysis showed the most popular resources used in general and secondary schools [11], [23], [28], [34], [45], [49].…”
Section: Web Technologies In Special Educationmentioning
confidence: 99%
“…They are used as an alternative to desktop apps. Research analysis showed the most popular resources used in general and secondary schools [11], [23], [28], [34], [45], [49].…”
Section: Web Technologies In Special Educationmentioning
confidence: 99%